The Importance of Changing Abusive Behavior to Prevent Domestic Violence - Michailovič, Ilona (Teisė, 2020)
The importance of working with domestic abusers is being analysed in the article. The need for correction of violent behaviour, based on international standards and empirical research, is emphasized by teaching perpetrators of domestic violence to adopt non-violent behaviour in interpersonal relationships with a view to changing violent behavioural patterns.